Code-switching and Its Relation to Language Acquisition : A Study of L1 Indonesian and L2 English - Nila Ulfah, Khanandya; Br.Perangin-angin, Alemina (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study examines the role of Indonesian–English code-switching in the process of second-language acquisition by synthesizing findings from previous research using a qualitative library method. The analysis shows that code-switching is a prominent linguistic practice in Indonesian educational and social contexts, serving multiple pedagogical, cognitive, and pragmatic functions. The findings reveal that code-switching operates as a cognitive scaffold, helping learners comprehend difficult English input by linking new information to familiar linguistic structures. It also reduces anxiety and increases classroom interaction, enabling students to participate more confidently during English lessons. In addition, frequent exposure to bilingual communication facilitates incidental vocabulary learning and contributes to the development of pragmatic competence, particularly through digital and peer interactions. However, the study also identifies potential drawbacks of excessive switching, including reduced English immersion and the emergence of hybrid morphological forms that may hinder grammatical accuracy. These findings highlight the complex and dual nature of code-switching: it is beneficial when used strategically but may become a barrier when overused. Overall, the study concludes that effective English language pedagogy in Indonesia requires a balanced approach that recognizes the supportive role of L1 while ensuring adequate exposure to English for long-term acquisition.